Diversidade de Larvas de Leptophlebiidae (Insecta: Ephemeroptera) da Reserva Florestal Adolpho Ducke, Manaus, AM. - Claudio Rabelo dos Santos-Neto (EntomoBrasilis, 2008)
ResumoA Reserva Florestal Adolpho Ducke (RFAD) é um fragmento de 10.000 hectares em conflito geográfico com a cidade de Manaus. O conhecimento da diversidade dos Ephemeroptera na RFAD é fundamental uma vez que estes organismos são elementos biológicos importantes; como importante fonte de alimento e, por seu potencial como indicadores das perturbações antropogênicas. Neste estudo teve-se como objetivo o levantamento da fauna de Leptophlebiidae (Ephemeroptera) das duas bacias hidrográficas, comparando a diversidade entre as bacias e entre os períodos seco e chuvoso. Coletou-se em 38 pontos dos igarapés das bacias Leste (Ipiranga, Uberê e Tinga) e a Oeste (Acará e Bolívia) da RFAD com rede entomológica aquática (rapiché). Para verificar diferenças na riqueza das duas bacias e, comparar a riqueza nos períodos seco e chuvoso foi feito o Índice de Riqueza de Jackknife. Foram obtidas 804 larvas de Leptophlebiidae sendo identificados 368 indivíduos e reconhecidos sete gêneros: Hagenulopsis Ulmer (35%; n=128); Thraulodes Ulmer (34%; n=124); Farrodes Peters (13%; n=48); Miroculis Edmunds Jr (12%; n=45); Hydrosmilodon Flowers & Dominguez (5%; n=19); Hermanella Needham & Murphy (0.8%; n=3), Microphlebia Savage & Peters (n=1). Este representa o primeiro registro de Hydrosmilodon, Hermanella e Microphlebia para a RFAD. Na comparação entre as bacias Leste e Oeste, o Índice de Riqueza de Jackknife não indicou diferença significativa na riqueza de gêneros. Hermanella e Hydrosmilodon não ocorreram na bacia Oeste e, Microphlebia não ocorreu na bacia Leste, no entanto estas ausências não representam diferença significativa na riqueza taxonômica das bacias. A comparação na riqueza de espécie de Leptophlebiidae considerando o período seco e chuvoso revelou uma diferença significativa entre os períodos. Cerca de 68% dos indivíduos foram coletados no período seco provavelmente porque neste período a água fica restrita ao canal do igarapé fornecendo substrato estável (vegetação marginal e folhiço) para a manutenção da fauna. No período chuvoso o substrato é carreado pelas enxurradas não sendo possível manutenção da fauna.Diversity of Larve Leptophlebiidae (Insecta: Ephemeroptera) of the Adolpho Ducke Forest Reserve, Manaus, AM.Abstract. The Adolpho Ducke Forest Reserve (ADRF) is a fragment of 10.000 hectares in geographic conflict with the city of Manaus. The knowledge of the diversity of Ephemeroptera in the ADRF is essencial because these organisms are biological important elements as food source and for its potential as indicative of the human disturbances. The objective of this study was to develop a survey of the diversity of Leptophlebiidae from two basins of ADRF, comparing the diversity between basins and the dry and rainy periods 38 points were collected from streams of the Eastern (Ipiranga, Uberê and Tinga) and Western (Acará and Bolivia) ADRF basins with aquatic entomological net (rapiché). To verify differences in the wealth of the two basins and to compare the wealth in the dry and rainy periods it was utilized the Jackknife wealth index. It was colleded 804 larvae of Leptophlebiidae, being identified 368 individuals from seven genera: Hagenulopsis Ulmer (35%; n=128); Thraulodes Ulmer (34%; n=124); Farrodes Peters (13%; n=48); Miroculis Edmunds Jr (12%; n=45); Hydrosmilodon Flowers & Dominguez (5%; n=19); Hermanella Needham & Murphy (0.8%; n=3), Microphlebia Savage & Peters (n=1). It represents the first register of Hydrosmilodon, Hermanella and Microphlebia for the ADRF. In the comparison between the basins East and West, the Jackknife’s did not indicate significant difference in the wealth of genera. Hermanella and Hydrosmilodon had not occurred in the West basin and, Microphlebia did not occurred in the East basin, however these absences does not represent significant difference in the taxonomic wealth of the basins. The comparison in the wealth of species of Leptophlebiidae considering the dry and rainy period revealed significant difference. About 68% of the individuals had been collected in the dry period, probably because in this period the water is restricted to the stream channel supplying steady substratum (marginal and leaf litter vegetation) to maintain the fauna. In the rainy period the substratum is carried down stream by torrents being impossible to maintain the fauna.